2015
DOI: 10.1111/spc3.12175
|View full text |Cite
|
Sign up to set email alerts
|

Trait Extraversion and Dopamine Function

Abstract: An inf luential theory within personality neuroscience suggests that trait extraversion is underpinned by individual differences in dopamine function. In a review of the relevant literature, we evaluate this theory in light of the evidence from molecular genetics, neuroimaging, and psychopharmacology. Evidence linking individual differences in extraversion with dopamine-relevant genes, structural volume of dopamine-rich brain regions (e.g., in striatal and ventral prefrontal areas), dopamine receptor availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
63
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(73 citation statements)
references
References 102 publications
9
63
1
Order By: Relevance
“…The present observations that the extraversion correlations on both the behavioral and physiological levels (measure of stability‐flexibility derived from AX‐CPT reaction times and ASY) are completely reversed under the selective D2 receptor blocker sulpiride provides further support for the DA theory of extraversion (Depue & Collins, ; Wacker & Smillie, ) and extends Wacker et al's (, ) prior findings by (a) showing that the modulating effects of sulpiride on the association between extraversion‐spectrum traits and ASY is not restricted to males and self‐ratings of personality but generalizes to females and partner ratings of personality, and by (b) providing initial evidence for the suggestion that previously reported differences between introverts' and extraverts' performance in n ‐back working memory tasks (Lieberman & Rosenthal, ; Wacker et al, ) may result from individual difference in the stability‐flexibility balance. The latter suggestion will be further probed using data from the same research project by examining the multivariate associations between the stability‐flexibility measure analyzed in the present report, performance in the n ‐back task, an alternative measure of stability‐flexibility derived from a different task (Dreisbach & Goschke, ), an indicator of the potentially related dimension of broad versus narrow cognitive scope (Gable & Harmon‐Jones, ), and dopaminergic candidate genes previously associated with both stability‐flexibility (Colzato et al, ; Markett, Montag, Walter, Plieger, & Reuter, ) and extraversion spectrum traits (Smillie, Cooper, Proitsi, Powell, & Pickering, ; Wacker, Mueller, Hennig, & Stemmler, ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The present observations that the extraversion correlations on both the behavioral and physiological levels (measure of stability‐flexibility derived from AX‐CPT reaction times and ASY) are completely reversed under the selective D2 receptor blocker sulpiride provides further support for the DA theory of extraversion (Depue & Collins, ; Wacker & Smillie, ) and extends Wacker et al's (, ) prior findings by (a) showing that the modulating effects of sulpiride on the association between extraversion‐spectrum traits and ASY is not restricted to males and self‐ratings of personality but generalizes to females and partner ratings of personality, and by (b) providing initial evidence for the suggestion that previously reported differences between introverts' and extraverts' performance in n ‐back working memory tasks (Lieberman & Rosenthal, ; Wacker et al, ) may result from individual difference in the stability‐flexibility balance. The latter suggestion will be further probed using data from the same research project by examining the multivariate associations between the stability‐flexibility measure analyzed in the present report, performance in the n ‐back task, an alternative measure of stability‐flexibility derived from a different task (Dreisbach & Goschke, ), an indicator of the potentially related dimension of broad versus narrow cognitive scope (Gable & Harmon‐Jones, ), and dopaminergic candidate genes previously associated with both stability‐flexibility (Colzato et al, ; Markett, Montag, Walter, Plieger, & Reuter, ) and extraversion spectrum traits (Smillie, Cooper, Proitsi, Powell, & Pickering, ; Wacker, Mueller, Hennig, & Stemmler, ).…”
Section: Discussionsupporting
confidence: 86%
“…At the very least, the present findings further bolster Wacker and Smillie's () conclusion that the link between extraversion and individual differences in DA is now already quite firmly established, and that it is time for research to move beyond the mere demonstration of this association by focusing on “(1) the causal role of dopamine in extraverted behavior, (2) the specificity of the association to agentic extraversion (vs. affiliative extraversion and other traits) and to particular features of dopamine functioning, (3) the mediating neural and psychological processes, and (4) the (moderating) contributions of other neurochemical systems” (Wacker & Smillie, , p. 233).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Pharmacological manipulations of dopamine thus represent an important new research direction. Indeed, such manipulations have already been fruitfully applied in the study of dispositional traits (e.g., Wacker and Smillie, 2015) and their application in the study of motivational states would seem a natural extension. Pharmacological manipulations of dopamine may, for example, allow researchers to more precisely decode the neural mechanisms that mediate the undermining effect of externally contingent rewards on intrinsic motivation.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike Extraversion and Neuroticism, which have been extensively studied in personality neuroscience because of their links to basic reward and threat processes and their inclusion in older personality models (for reviews, see Allen & DeYoung, 2017;Shackman, Tromp, Stockbridge, Kaplan, Tillman, & Fox 2016;Wacker & Smillie, 2015), Agreeableness has received relatively little attention. Two small resting state fMRI studies found that Agreeableness is positively associated with functional connectivity within major hubs of the default network (Adelstein et al, 2011;Sampaio et al, 2014), a finding consistent with the theory that understanding and anticipating the mental states of others is facilitated by this network (Andrews-Hanna, Smallwood, & Spreng, 2014).…”
mentioning
confidence: 99%